2015
DOI: 10.1039/c5rp00068h
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of a discrepant event in changing the conceptions of evaporation and boiling in elementary school students

Abstract: The purpose of this study was to explore how examples used in teaching may influence elementary school students' conceptions of evaporation and boiling. To this end, the examples traditionally used to explain evaporation and boiling in Korean 4th grade science textbooks were analyzed. The functions of these published examples were explanation (empirical recognition, identification, and evidence) and reinforcement (applications). However, few reinforcement functions (such as comparison and supposition) or clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Consistent with existent literature (Costu, 2008;Çalık, 2008;Paik, 2015), the present study showed that preservice science teachers possessed a range of ACs and SUs about boiling. Looking at ACs that are particularly related to macro level (i.e., sensual changes) (Unal, Calik, Ayas, & Coll, 2006), we can argue that most of the participants could easily envisage joint existence of water vapor, heat and boiling and condensing vaporized air when it encounters cold water.…”
Section: Conceptual Difficulties About Boilingsupporting
confidence: 91%
“…Consistent with existent literature (Costu, 2008;Çalık, 2008;Paik, 2015), the present study showed that preservice science teachers possessed a range of ACs and SUs about boiling. Looking at ACs that are particularly related to macro level (i.e., sensual changes) (Unal, Calik, Ayas, & Coll, 2006), we can argue that most of the participants could easily envisage joint existence of water vapor, heat and boiling and condensing vaporized air when it encounters cold water.…”
Section: Conceptual Difficulties About Boilingsupporting
confidence: 91%
“…The researchers reported that the question-answer technique was an effective method in eliminating students' misconceptions about the concepts of melting and dissolution. Paik (2015) examined the role of examples in 4th grade textbooks used as textbooks in Korea on students' perceptions of the concepts of evaporation and boiling. In the study conducted with fourth, fifth and sixth grade students, it was revealed that many students thought that evaporation events under heating conditions were boiling, while the same events without an obvious heating source were evaporation.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Since the PSTs generally consider external pressure atmospheric pressure, they think the external pressure remains the same as long as the environment does not change. Students often associate boiling with temperature, and the boiling of a liquid is evaluated according to the height of the sea level (Şimşek, Öztuna-Kaplan, Çorapçıgil & Mısırlı, 2018;Paik, 2015). In scientific terms, giving the essence of the event can minimize this problem.…”
Section: Discussionmentioning
confidence: 99%